Un-Plasticized Polyvinyl Chloride and its Growth on Nepalese Market - Shrestha, Ankit; Neupane, Sudan; Aryal, Lekhnath (Journal of Innovations in Engineering Education, 2020)
The paper presents an overview of some marketing strategies that are strongly influencing on the Nepalese un-plasticized poly vinyl chloride door and windows market. The result of the study reveals that product quality improvement is one of the important products related marketing strategies in the doors and windows market of Nepal and addition of new features. The study also reveals that advertisements and exhibitions/meets are two important promotional strategies influencing the consumers in their purchase. This study followed a judgmental sampling technique. The study shows that there is enough evidence to indicate that the brand preference is dependent on market segment in un-plasticized poly vinyl chloride windows in Kathmandu Valley market. Upon the analysis of the product delivery report of the past five years the market seems to be growing at an average rate of 25% annually. Un-plasticized poly vinyl chloride has comparative advantage over wood and aluminum profiles on technical, physical as well as overall performance comparison hence proving to be a better material for doors and windows.